The Temporalis Muscle Flap for Palate Reconstruction: Case Series and Review of the Literature - Brennan, Tara; Tham, Tristan M.; Costantino, Peter (International Archives of Otorhinolaryngology, 2017)
Introduction The temporalis myofascial (TM) is an important reconstructive flap in palate reconstruction. Past studies have shown the temporalis myofascial flap to be safe as well as effective. Free flap reconstruction of palate defects is also a popular method used by contemporary surgeons. We aim to reaffirm the temporalis myofascial flap as a viable alternative to free flaps for palate reconstruction.Objective We report our results using the temporalis flap for palate reconstruction in one of the largest case series reported. Our literature review is the first to describe complication rates of palate reconstruction using the TM flap.Methods Retrospective chart review and review of the literature.Results Fifteen patients underwent palate reconstruction with the TM flap. There were no cases of facial nerve injury. Five (33%) of these patients underwent secondary cranioplasty to address temporal hollowing after the TM flap. Three out of fifteen (20%) had flap related complications. Fourteen (93%) of the palate defects were successfully reconstructed, with the remaining case pending a secondary procedure to close the defect. Ultimately, all of the flaps (100%) survived.Conclusion The TM flap is a viable method of palate defect closure with a high defect closure rate and flap survival rate. TM flaps are versatile in repairing palate defects of all sizes, in all regions of the palate. Cosmetic deformity created from TM flap harvest may be addressed using cranioplasty implant placement, either primarily or during a second stage procedure.
Keywords: reconstructive surgical procedures; palate; temporal muscle